Mechanical behaviour and durability of high volume fly ash cementitious composites (Fracture and Structural Integrity, 2016)
The purpose of this research is to separate different morphological particles of ASTM class F fly ash, and study their effect on mechanical behaviour and durability of high volume cementitious mixtures. In this research wet separation of raw fly ash is carried out, which resulted in three layers of different morphological particles. The first layer of particles float, comprise of about 1-5% of fly ash, is identified as cenospheres or hollow spheres. The second layer of particles is measured to be 55-60% of raw fly ash and consisting of porous spherical and rounded particles rich in Si and Al. The third layer particles is measured to be about 35-40% of raw fly ash. High volume fly ash cementitious composites containing second or third layer particles are tested under compression and bending, highlighting a higher strength and ductility in comparison to cementitious ones containing raw fly ash particles.
Keywords: Cementitious matrix; Raw fly ash; Second layer particles; Third layer particles